2012
DOI: 10.1007/s12600-012-0264-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of downy mildew of sweet basil (Ocimum basilicum) caused by Peronospora belbahrii by means of resistance inducers, fungicides, biocontrol agents and natural products

Abstract: In the present study a number of compounds (acibenzolar-S-methyl, mineral and organic 12 fertilizers, plant extracts), known for their capability of inducing resistance in plants to several 13 pathogens, were tested in 2011 and 2012, in comparison with registered fungicides, cupper-based 14 fungicides and biocontrol agents, to control downy mildew of sweet basil (Ocimum basilicum L.), 15 incited by Peronospora belbahrii. Four experimental trials were carried out under glasshouse 16 conditions in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
3
24
0
3
Order By: Relevance
“…In the present work, the effectiveness of acibenzolar-S-methyl applied as seed treatment was investigated. Previous study reported the ability of acibenzolar-S-methyl to provide reduction of downy mildew of basil when applied as leaf spray in greenhouse (Mersha et al 2012;Gilardi et al 2013). Our data demonstrated that acibenzolar-S-methyl applied as seed treatment at 0.05 mg/kg of seeds significantly reduces downy mildew incidence on basil without any negative effect on seed quality.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the present work, the effectiveness of acibenzolar-S-methyl applied as seed treatment was investigated. Previous study reported the ability of acibenzolar-S-methyl to provide reduction of downy mildew of basil when applied as leaf spray in greenhouse (Mersha et al 2012;Gilardi et al 2013). Our data demonstrated that acibenzolar-S-methyl applied as seed treatment at 0.05 mg/kg of seeds significantly reduces downy mildew incidence on basil without any negative effect on seed quality.…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, the use of chemicals in the field is complicated by the scalar type of harvest, which makes very difficult to comply with the intervals required between the last treatment and harvest. In fact, being the causal agent of the disease very aggressive, field sprays, even when carried out with the most effective products, provide a only partial control under severe disease pressure (Gilardi et al 2013;Homa et al 2014) and are not considered the wisest control methods, because of the risk of selection of strains of the pathogen resistant to the fungicides having a specific mode of action.…”
Section: Introductionmentioning
confidence: 99%
“…El uso de otro inductor de resistencia adquirida, acibenzolar-S-methyl (ASM) en dosis de 5 mg/L tres veces por semana, redujo la incidencia en 93.8% y el uso del ácido aminobutírico DL-3 en dosis de 125 mg/L redujo la incidencia en comparación con el testigo. Al igual que en el estudio anterior, el uso de acibenzolar-S-methyl (ASM) fue efectivo para controlar la enfermedad en comparación con otros inductores de resistencia, controladores biológicos y productos naturales (Gilardi et al 2013).…”
Section: Resultados Y Discusiónunclassified
“…Al igual que los otros tratamientos, el Bacillus subtilis no controló la enfermedad. Un estudio reciente probó el uso de fungicidas a base de cobre, agentes naturales, inductores de resistencia y controladores biológicos (Gilardi et al 2013). Al igual que en este estudio, el Bacillus subtilis no fue efectivo para controlar Peronospora belbahrii en albahaca.…”
Section: Resultados Y Discusiónunclassified
“…Because no cultivars of marketable interest are known to be resistant or tolerant to downy mildew (Ben‐Naim et al ., ), the control of downy mildew is mainly based on the application of fungicides such as mefenoxam, potassium phosphite, mandipropamid, fluopicolid, mancozeb and azoxystrobin (Gilardi et al ., , ; Wyenandt et al ., ). Furthermore, the resistance inducer acibenzolar‐ S ‐methyl significantly reduces the disease (Gilardi et al ., ; Mersha et al ., ). The use of chemicals in the field is complicated by the continuous nature of the harvest, and by the high risk of development of pathogen strains resistant to the fungicides through specific modes of action.…”
Section: Downy Mildew Of Basilmentioning
confidence: 99%